2021
DOI: 10.52168/bjf.2021.33.17
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fishing gears and crafts used for harvesting the Asian seabass, Lates calcarifer along the Bay of Bengal, Bangladesh coast

Abstract: Though Asian Seabass, which is locally known as "Koral"/"Vetki," is a vital species in terms of its popularity and price, little is known about the location of breeding and nursery ground, peak breeding season, peak harvesting season, population dynamics, harvesting operation (gears and crafts used for harvesting) of this species in Bangladesh. An investigation was carried out to enlist the group of crafts and gears that are being operated on the Bay of Bengal coast by the fishermen for Asian seabass harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…However the study of Ali et al (2015) suggested that, fishermen were used gill net, cast net, fixed purse net, seine net, dip net, lift net and drag/ push net for fishing activity in Lohalia River in Patuakhali. Some other studies were also found similar types of fishing gears, for instance, Bay of Bengal (Haque et al, 2021), Surma River, Sylhet district (Mia et al, 2018), Ashura beel, Dinajpur (Ferdoushi et al, 2018), and Hatiya Island (Azam et al, 2014). During monsoon when water level increased the use of all types of gears was also increased simultaneously.…”
Section: Feed Analysis Of Fishermen Communitymentioning
confidence: 65%
“…However the study of Ali et al (2015) suggested that, fishermen were used gill net, cast net, fixed purse net, seine net, dip net, lift net and drag/ push net for fishing activity in Lohalia River in Patuakhali. Some other studies were also found similar types of fishing gears, for instance, Bay of Bengal (Haque et al, 2021), Surma River, Sylhet district (Mia et al, 2018), Ashura beel, Dinajpur (Ferdoushi et al, 2018), and Hatiya Island (Azam et al, 2014). During monsoon when water level increased the use of all types of gears was also increased simultaneously.…”
Section: Feed Analysis Of Fishermen Communitymentioning
confidence: 65%
“…The latest iteration of seabass aquaculture in Bangladesh In Bangladesh's coastal region, seabass cultivation in freshwater ponds and cage culture in rivers and estuaries has started. Larvae fry, and fingerlings of seabass are collected with different kinds of nets, such as set bag nets and small mosquito nets (Haque et al, 2021;Azam et al, 2014;Siddik et al, 2016c) in the river estuaries, rivers, and pastures along the coasts of Khulna, Patuakhali, Barisal, Satkhira, and Cox's Bazar districts of Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Mia et al (2018) discovered 16 types of fishing gears from Surma River Sylhet, some other studies such as, 30 fishing gears from Chalan Beel (Sultana and Islam, 2016), 28 fishing gears from Ashura beel, Dinajpur (Ferdoushi et al, 2018) were identified for catching fishes. Whereas 10 fishing gears were used to catch Asian seabass at the coastal area of Bangladesh (Haque et al, 2021).…”
Section: Fish Biodiversity and Fishing Gears Used In Jhapa Baormentioning
confidence: 99%